Breast Hematoma: An Under-Recognized and Under-Reported Female-Specific Traumatic Injury and Its Clinical Significance. Issue 1 (January 2021) - Hashmi, Danielle LaSalle; Ong, Adrian W.; Muller, Alison; Itzoe, MariaLisa; Martin, Anthony; Foster, Shannon Marie
Female-specific traumatic injury patterns have not been well researched and are potentially not well documented. Our aim was to examine the prevalence of breast hematomas (BHs) after blunt chest trauma, and to evaluate if there were risk factors associated with BH requiring intervention. A retrospective review from 2013 to 2018 was performed, identifying female patients ≥18 years sustaining blunt chest trauma. BH was defined as the presence of a collection of blood within the breast parenchyma, and clinically significant breast hematoma (CSBH) as BH requiring blood transfusion, surgical, or interventional radiology intervention. Univariate analysis was performed comparing CSBH with BH in terms of demographics, injury severity, antithrombotic agent use, and body mass index (BMI). Of 871 female patients meeting criteria, 59 (7%) had BH. Of these, 10 (17%) had CSBH (transfusion only, n = 3; angioembolization, n = 4; operation, n = 3). Compared to BH not requiring intervention, CSBH patients were older (mean age, 80 vs 69, P = .006), but had similar rates of motor vehicle crashes (90% vs 78%), seatbelt use (70% vs 71%), antiplatelet use (10% vs 12%), and anticoagulant use (10% vs 6%). Median Injury Severity Scores and median BMI (34 vs 34) were similar between the groups.